Study of Microstructure and Corrosion Behavior of AH36 FSW Welds and HSLA S690 ARC Weld - Μπούτσαλη, Βασιλική (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών, 2016)
This thesis is entitled “Study of microstructure and corrosion behavior of AH36 FSW welds and HSLA S690 ARC welds”. The experiments took place at the Shipbuilding Technology Laboratory of the school of Naval Architecture and Marine Engineering at National Technical University of Athens. The purpose of the thesis is to study and compare the corrosion behavior of arc welding, a conventional welding method, with the friction stir welding, a new method of welding in shipbuilding. Thus, within the present thesis, the microstructure and the corrosion behavior of the above two welds were studied. Moreover, for these welds, two different shipbuilding steels have been used: the common shipbuilding steel (AH36) and a high strength low alloy steel, (HSLA - S690). The HSLA steels are used in recent years in Shipbuilding, as they exhibit improved properties concerning mechanical properties and particularly on the fatigue strength. Specifically, the metallography of the welds and their micro-hardness are studied initially and then, their corrosion behavior. The study of corrosion was made by two methods: electrochemical and standardized methods of accelerated aging in a salt spray chamber. The electrochemical methods, which were used are the following: the linear polarization, the Tafel and the method of electrochemical impedance. Furthermore, it was attempted to measure the three-dimensional shape of a corroded specimen’s surface and compare it with the surface of a non-corroded one, by using a structured white light 3D scanner. Finally, substantial conclusions which have arisen through the entire course of this research are noted.